Rendimentos de cortes, proporção tecidual da carcaça e composição centesimal da carne de caprinos jovens em função do grupo racial e do peso corporal de abate - Marques, R.o. [UNESP]; Menezes, J.j.l. [UNESP]; Gonçalves, H.c. [UNESP]; Medeiros, B.b.l. [UNESP]; Rodrigues, L. [UNESP]; Canizares, G.i.l. [UNESP]; Gomes, H.f.b.; Roça, R.o. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2013)
The purpose of this study was to evaluate the commercial cuts, loin tissues and composition proportions in meant from five racial groups: Alpine, ½ Boer + ½ Alpine (½ BA), ½ Anglo Nubian + ½ Alpine (½ ANA), ¾ Boer + ¼ Alpine (¾ BA), ¼ Boer + ¼ Alpine + ½ Anglo Nubian (Tricross), submitted to three slaughter weights (25, 30 and 35kg) in feedlot, using a complete diet. The crossing of Boer and Anglo Nubian with Alpine females only improved, in kids, the yield of cuts considered third category such as neck and rib. Slaughter body weights between 30 and 35kg should be preferred due to increase in the proportion of the loin, reduction in the proportion of the neck in Alpine and increase in the leg in Alpine and ¾ Boer, beyond the appropriate amounts of intermuscular fat and muscle.

O objetivo do presente trabalho foi avaliar as proporções de cortes comerciais, tecidos do lombo e composição da carne de cabritos de cinco grupos raciais: Alpino, ½ Boer + ½ Alpino (½ BA), ½ Anglo Nubiano + ½ Alpino (½ ANA), ¾ Boer + ¼ Alpino (¾ BA), ¼ Boer + ¼ Alpino + ½ Anglo Nubiano (Tricross), submetidos a três pesos de abate (25, 30 e 35kg) em sistema de confinamento, com utilização de dieta completa. O cruzamento das raças Boer e Anglo Nubiana com fêmeas Alpinas apenas melhorou, nos cabritos, os rendimentos de cortes considerados de terceira categoria, como pescoço e costela. Pesos corporais de abate entre 30 e 35kg devem ser preferidos por aumentarem a proporção de lombo, reduzirem a proporção de pescoço nos Alpinos e aumentarem a de perna em Alpinos e ¾ Boer, além de proporcionarem quantidades adequadas de músculo e gordura intermuscular.
Cut yields, carcass and tissue composition proportion in meat from young goats depending on the breed and slaughter body weight
Keywords: cabrito; cortes comerciais; músculo; osso; bone; commercial cuts; kid; muscle